Working capital management and return on assets of manufacturing industry of Peru - Ames Porras, Marianela Roxana (2020)
This article contributes to the increase in knowledge and existing theory about the administration of working capital and its relation to profitability. Using a sample of 23 companies listed on the Lima stock exchange during the period 2009-2018. There is a negative relationship between profitability (ROA) and the average inventory period (PPI), in the same way a negative relationship between profitability and the average collection period (PPC), finally a positive relationship between profitability and the period average payment (PPP). It is concluded that a company of the industrial sector in Peru, manages to be more efficient, effective and competitive insofar as it improves the management of working capital, which is achieved if it achieves effective management of financial resources, an equitable policy of Customer credit, proper inventory management and proper management of supplier leverage and short term.